Analisis Pernikahan Cinta Buta di Kabupaten Batu Bara - Alang Sidek (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
Marriage is a very sacred thing, the fiqh scholars define marriage is to have something through the path prescribed in religion, with the aim of according to human tradition. According to Islamic Shari'a is to justify something, but this is not the highest purpose of marriage in Islamic Shari'a. The highest goal is to maintain regeneration, maintain human genes, and each husband and wife get peace of mind because love and affection can be channeled. This rule regarding marriage is actually to respect women and to distinguish between humans and animals, because with the rules regarding marriage, the children of human descendants in this world will be maintained their glory and the purpose of the marriage will be achieved. The research method used in this research is by means of field research or field research. Research that is directly carried out in the field or on the respondent. The data obtained from the study were analyzed descriptively, namely research that seeks to describe current problem solving based on data. From this research, it can be concluded that the perception of Islamic Boarding School leaders towards Blind Chinese Marriage with the results of interviews with the leaders of the Salafiyah Islamic Boarding School Guntur Darul Salam: Justify the implementation of blind Chinese marriage (tahlil) with hilah or legal reasons that have been outlined by Syafi'i, namely by hiding the intention of tahlil, Batu Bara Regency, especially the Malay community, who are mostly Syafi'i sects, think that blind marriage is something that is allowed if needed. Everything that has been prescribed and prohibited by Allah SWT must have a specific purpose and purpose, even the scholars of usul fiqh discussed it in a discussion, namely in the matter of Maqasid Al-Shariah, one of which is maintaining offspring. Keywords: Marriage, Cinta Buta, Kabupaten, Batu Bara.